Non-fusion rates in anterior cervical discectomy and implantation of empty polyetheretherketone cages - Pechlivanis, Ioannis; Thuring, Theresa; Brenke, Christopher; Seiz-Rosenhagen, Marcel; Thomé, Claudius; Barth, Martin; Harders, Albrecht; Schmieder, Kirsten (Spine, 2011)
STUDY DESIGN: A prospective analysis. - OBJECTIVE: Our aim was to assess the radiographically detectable bony fusion in patients with anterior cervical discectomy (ACD) and polyetheretherketone (PEEK)-cage implantation without additional filling. Furthermore, clinical data of patients with and without fusion were compared. - SUMMARY OF BACKGROUND DATA: PEEK-cage implantation is performed in cervical spinal surgery because of its benefits. However, fusion rates without filling of the cage have not been reported. - METHODS: Patients selected for ACD with PEEK-cage implantation prospectively underwent plain radiography in anterior-posterior and lateral projections during the postoperative hospital stay and at follow-up. Furthermore, clinical status was evaluated using the Odom scale, the Short Form-36, the Visual Analog Scale (VAS) for arm and neck pain, and the cervical Oswestry score. Fusion status, migration, and subsidence of the PEEK cage were evaluated on the basis of the lateral radiographs. Fusion was confirmed by presence of continuous trabecular bone bridges in the disc space. To exclude an influence of the cage on the evaluation of fusion rates, fusion was evaluated in analogous fashion retrospectively in a control group. - RESULTS: A total of 52 patients underwent ACD and interbody fusion. One-level surgery was performed in 44 patients and 2-level surgery in 8 patients. A total of 60 ACD and interbody fusions with a PEEK cage were analyzed. A majority of operations were at the C5/6 level (40 patients, 77%). Cage height was 4 mm in 32 cases, 5 mm in 23 cases, and 6 mm in 5 cases. Bony fusion was present at 43 treated levels (71.7%), whereas at 17 levels (28.3%) no fusion was found. Statistical analysis revealed no significant difference between the fusion and non-fusion groups regarding time to follow-up, implanted cage height. Short Form-36, cervical Oswestry score, VAS arm and neck, or Odom criteria. In the control group, ACD was performed in 29 patients (42 levels; 18 one-level and 12 two-level operations). Bony fusion was present at 30 levels (71.4%), whereas non-fusion was present at 12 treated levels (28.6%). Statistically analysis revealed no significant difference between the study group and the control group regarding time to follow-up or fusion rates. - CONCLUSION: Implantation of empty PEEK cages after ACD shows an unexpectedly low rate effusion according to radiologic criteria, although no statistically significant difference could be observed clinically.